COMPARISON OF LAWS REGULATION OF PROFESSIONAL ORGANIZATIONS OF ADVOCATES IN INDONESIA AND MALAYSIA : PERBANDINGAN HUKUM PENGATURAN ORGANISASI PROFESI ADVOKAT DI INDONESIA DENGAN MALAYSIA - Selly, Grees (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
Advocates are one of the main pillars in law enforcement in Indonesia. To strengthen the existence of advocates as the main pillar of law enforcement, Law No. 18 of 2003 concerning Advocates was established. The purpose of establishing the Advocates Law is to provide guarantees of professionalism, independence and independence of the profession by upholding the principles of the rule of law and the constitution. Regulating the advocate profession is very difficult. Since the Advocates Law was enacted until now, there have been frequent incidents within the advocate profession that have ended in judicial review to the Constitutional Court. The conflicts that often occur are related to the interpretation of the provisions of the article concerning advocate organizations. Initially, advocates designed advocate organizations with a single organizational system as formulated in Article 28 paragraph (1) of the Advocates Law which states that: